BamA and BamD Are Essential for the Secretion of Trimeric Autotransporter Adhesins - Rooke, Jessica L.; Icke, Christopher; Wells, Timothy J.; Rossiter, Amanda E.; Browning, Douglas F.; Morris, Faye C.; Leo, Jack C.; Schütz, Monika S.; Autenrieth, Ingo B.; Cunningham, Adam F.; Linke, Dirk; Henderson, Ian R. (Frontiers in Microbiology, 2021)
The BAM complex in Escherichia coli is composed of five proteins, BamA-E. BamA and BamD are essential for cell viability and are required for the assembly of -barrel outer membrane proteins. Consequently, BamA and BamD are indispensable for secretion via the classical autotransporter pathway (Type 5a secretion). In contrast, BamB, BamC and BamE are not required for the biogenesis of classical autotransporters. Recently, we demonstrated that TamA, a homologue of BamA, and its partner protein TamB, were required for efficient secretion of proteins via the classical autotransporter pathway. The trimeric autotransporters are a subset of the Type 5-secreted proteins. Unlike the classical autotransporters, they are composed of three identical polypeptide chains which must be assembled together to allow secretion of their cognate passenger domains. In contrast to the classical autotransporters, the role of the Bam and Tam complex components in the biogenesis of the trimeric autotransporters has not been investigated fully. Here, using the Salmonella enterica trimeric autotransporter SadA and the structurally similar YadA protein of Yersinia spp., we identify the importance of BamA and BamD in the biogenesis of the trimeric autotransporters and reveal that BamB, BamC, BamE, TamA and TamB are not required for secretion of functional passenger domain on the cell surface.